Seed coat and fruit surface micromorphology of some Cynoglossum L. (Boraginaceae) species (Bangladesh Journal of Botany, 2008)
Fruits and seeds of Cynoglossum creticum Miller, C. officinale L., C. montanum L. and C. glochidiatum Wallich) distributed in the Middle and East Black Sea Region in Turkey were studied by scanning electron microscopy. Some differences were found in seed coats and fruit surfaces. SEM observations of fruit surface were focused on surface ornamentation and glochids. Two types (tuberculate and granulate) and two subtypes (granulate - punctuate and granulate - tuberculate) were observed among the species. Reticulate type of seed coat and detailed subtypes of reticulate types were determined on the basis of ornamentation of the seed coats. Key words: Cynoglossum, Fruit surface, Seedcoat, SEM, Micromorphology, Boraginaceae doi:10.3329/bjb.v37i2.1716 Bangladesh J. Bot. 37(2): 115-119, 2008 (December)